(untitled) (Research, Society and Development, 2022)
The research developed aims to present, especially to pedagogues, the knowledge of the Institutional Psychopedagogy area of action, in addition to the work and referrals of the Psychopedagogue to students who have a diagnosis or indication of Specific Functional Disorders (SPT). This is a qualitative bibliographic and field research. Data collection was carried out through a semi-structured questionnaire, with an Institutional Psychopedagogue, who works at the Education Department of a municipality in the North of Paraná. From these surveys it was possible to know in greater depth the work of the Psychopedagogue in the school environment. The result of theoretical and field research demonstrates that inclusive public policies in the State of Paraná have been implemented in this municipality, albeit slowly due to objective conditions. It is also concluded that there is a need to overcome the barrier in communication between those involved in the school environment, given that the role of the Institutional Psychopedagogue is to work, in a reflective and critical way, with issues involved in the teaching organization process. and learning, seeking referrals and clues that help to overcome contextual obstacles, taking into account each one’s way of learning.